(3GdhbGFY hGdCacGQ GdEbJUGOjIs - (3eMehO(B, (3SMfhfs ((3GdbGgQI(B:s (3OGQ GdaLQ(B,s, 2006)
(3GdhbGFY hGdCacGQ GdEbJUGOjI aj YgO GdQShd(B((3U(B)-(3GdhbGFY hGdCacGQ GdEbJUGOjI aj YgO GdNdaGA GdQGTOjf(B-(3GdhbGFY hGdCacGQ aj GdJGQjN GdYQHj GdESdGejs
Keywords: (3GdCacGQ GdEbJUGOjIs; (3GdCacGQ GdEbJUGOjI GdESdGejIs; (3GdEbJUGO GdESdGejs; (3GdJGQjN GdESdGej GdEbJUGOjs